Identification of local organic soils based on cone penetration test results - Grzegorz Straż (Budownictwo i Architektura, 2014)
This paper presents the results of attempts to identify organic soils on the basis of test results performed under in situ conditions by cone penetration testing (CPT). The results of 439 selected tests were analysed which reflected the behaviour of local organic soils of organic matter ranging from 6,3 to 17,4%. Crucial to soil investigation were values measured of cone resistance (qc) and sleeve friction (fs) and the friction ratio (Rf) estimated according to those values. To identify organic soils, selected criteria were used, proposed among others by: Mayne, Marr, Bergmann, Schmertmann, Capanella and Robertson [2,5]. An analysis showed that an identification of organic soil types in terms of the present classification of standards, in view of the criteria used, is ambiguous and does not allow to identify them precisely by CPT.